PENGUATAN KAPABILITAS SUMBER DAYA MANUSIA LOKAL MELALUI PENDIDIKAN DAN PELATIHAN BAHASA MANDARIN BAGI PENGELOLA DTW TANAH LOT KABUPATEN TABANAN - I.G.N. Widyatmaja; I.M. Sendra; I.B.K. Astina; I.K. Suwena (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The development of tourists from China before the Covid-19 pandemic was very fast, especially in the Tanah Lot Tourist Destination, Tabanan Regency, Bali Province, but in terms of the ability to speak Mandarin for managers it was very low. Strengthening local human resource capabilities through Mandarin education and training referred to here is a basic skill that should be understood and practiced by each individual in a tourism business in order to be able to run their business in a sustainable manner. This activity aims to improve Chinese language skills for oral translators and provide basic Chinese language skills for local employees. Another goal is to provide an introduction to Chinese cultural values that are considered necessary for managers to know so that they are expected to assist in efforts to improve the quality of performance of Tanah Lot destination managers. Keywords : Management, Mandarin, Training, Strengthening, Participation, Tourism